The characterisation of diarrhoeagenic verotoxin producing non-o157 coli among young children in Kuantan, Malaysia - Karim Khan, Md Fazlul; Rashid, Shah Samiur; Aizi Nor Mazila, Ramli; Kabir, Muhammad Nomani; Hasan Maziz, Mohammad Nazmul (Penerbit Universiti Sains Malaysia, 2022)
Background: Diarrhoeagenic verotoxin producing non-O157 Escherichia coli (VTEC) are associated with endemic infantile diarrhoea-causing morbidity and mortality worldwide. VTEC can also cause severe illness and has an impact on outbreaks, especially in developing countries. This study aims to investigate the prevalence and characterisation of VTEC and their association in causing infectious diarrhoea among Malaysian children. Methods: Standard microbiological techniques identified a total of 137 non-repeated, clinically significant E. coli isolates. Serological assays discerned non-O157 E. coli serogroup, subjected to virulence screen (VT1 and VT2) by a polymerase chain reaction (PCR). Results: Different PCR sets characterised the 49 clinical isolates of sorbitol positive non-O157 E. coli. Twenty-nine isolates harboured verotoxin genes associated with diarrhoea among children (≤ 5 years old). Among the 29 (59.18%) strains of verotoxin producing E. coli* genotypes VT1 and VT2 were detected in 21 (42.85%) and 5 (10.20%) isolates respectively, while both VT1 and VT2 genes were confirmed in 3 (6.12%) isolates. Conclusion: This study evaluates on the prevalence, serological characteristics and antimicrobial susceptibility patterns of VTEC diarrhoea affected children (≤ 5 years old). Besides, the prevalence of verotoxin gene was determined as a root cause of diarrhoea among Malaysian children.